PENGARUH MEDIA PEMBELAJARAN FLASH CARD DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Yeheskiel Pratama; Irwan Setyowidodo; Yunus Tanthowi (CV. Kalimasada Group, 2025)
This study's overarching goal is to enhance the Pancasila Education learning outcomes for fourth graders at SDN Besuk 1 by means of a flash card learning medium. Thirteen students participated in the study over the course of two cycles, with classroom action research (CAR) serving as the research methodology. Planning, carrying out, and finishing are the three main phases that make up each cycle. Students in fourth grade at SDN Besuk 1 showed significant improvement in their learning outcomes when exposed to flash cards as a learning medium. The learning outcomes of the students have not yet attained the minimum completion criterion (KKM) at the pre-cycle stage. The results of the first two cycles of instruction have shown an improvement in student performance with the introduction of learning media. While 84% of learners were able to finish cycle II, 61% were able to do so in cycle I. The results show that using Flash Cards as a learning tool improved students' performance.